Investigation Into the Risk Factors Related to In-stent Restenosis in Elderly Patients With Coronary Heart Disease and Type 2 Diabetes Within 2 Years After the First Drug-Eluting Stent Implantation - Yi, Ming; Tang, Wen-hui; Xu, Shuai; Ke, Xiao; Liu, Qiang (Frontiers in Cardiovascular Medicine, 2022)
Background The present study aims to explore risk factors related to in-stent restenosis (ISR) in elderly patients with coronary heart disease and type 2 diabetes within 2 years after the first drug-eluting stent (DES) implantation. Methods This case-control study retrospectively analyzed the clinical data of patients with coronary heart disease and diabetes undergoing percutaneous coronary intervention (PCI) in Shenzhen Sun Yat-sen Cardiovascular Hospital between January 2010 and March 2020. Univariate and multivariate models were used to assess independent factors for DES-ISR. Categorical principal component analysis of clinical variables was performed to determine important components for DES-ISR. Nomogram was constructed to quantitatively predict the probability of DES-ISR development. The diagnostic potential of clinical variables was determined by receiver operating characteristic curve. Results In the derivation cohort, 1741 cases were included in this study, and a total of 227 pairs of cases and controls were generated by propensity score matching. In the validation cohort, 102 cases were included with 19 cases (18.6%) with DES-ISR. Glomerular filtration rate < 60 ml/min/1.73m2, fasting blood glucose ≥ 6.5mmol/L, multivessel coronary artery disease, coronary artery diffuse disease, PCI operation time (≥ 60 min), emergency PCI were associated with ISR. High Nomogram score was associated with the increased risk of ISR. Further analysis of the validation cohort showed that higher levels of HbA1c-coefficient of variation (CV) were significantly associated with the increased risk of ISR. HbA1c-CV exhibited good predictive ability for ISR in the validation cohort. Conclusions In conclusion, the fasting blood glucose level during the perioperative period of emergency PCI and the long-term variation of HbA1c during the follow-up period are related to the incidence of DES-ISR and the degree of stenosis. Reducing blood glucose fluctuations may decrease the risk of DES-ISR.